The feasibility, acceptability and preliminary efficacy of a low-cost, virtual-reality based, upper-limb stroke rehabilitation device: a mixed methods study. Issue 18 (28th August 2019) - Warland, Alyson; Paraskevopoulos, Ioannis; Tsekleves, Emmanuel; Ryan, Jennifer; Nowicky, Alexander; Griscti, Josephine; Levings, Hannah; Kilbride, Cherry
Abstract: Purpose: To establish feasibility, acceptability, and preliminary efficacy of an adapted version of a commercially available, virtual-reality gaming system (the Personalised Stroke Therapy system) for upper-limb rehabilitation with community dwelling stroke-survivors. Method: Twelve stroke-survivors (nine females, mean age 58 years, [standard deviation 7.1], median stroke chronicity 42 months [interquartile range 34.7], Motricity index 14–25 for shoulder and elbow) were asked to complete nine, 40-min intervention sessions using two activities on the system over 3 weeks. Feasibility and acceptability were assessed through a semi-structured interview, recording of adverse effects, adherence, enjoyment (using an 11-point Likert scale), and perceived exertion (using the BORG scale). Assessments of impairment (Fugl–Meyer Assessment Upper extremity), activity (ABILHAND, Action Research Arm Test, Motor Activity Log-28), and participation (Subjective Index of Physical and Social Outcome) were completed at baseline, following intervention, and at 4-week follow-up. Data were analysed using Thematic Analysis of interview and intervention field-notes and Wilcoxon Signed Ranks. Side-by-side displays were used to integrate findings. Results: Participants received between 175 and 336 min of intervention. Thirteen non-serious adverse effects were reported by five participants. Participants reported a high level of enjoyment (8.1 and 6.8 out of 10) and rated exertion between 11.6 and 12.9 out of 20. Themes of improvements in impairments and increased spontaneous use in functional activities were identified and supported by improvements in all outcome measures between baseline and post-intervention ( p < 0.05 for all measures). Conclusions: Integrated findings suggested that the system is feasible and acceptable for use with a group of community-dwelling stroke-survivors including those with moderately-severe disability. Implications for rehabilitation: To ensure feasibility of use and maintenance of an appropriate level of challenge, gaming technologies for use in upper-limb stroke rehabilitation should be personalised, dependent on individual need. Through the use of hands-free systems and personalisation, stroke survivors with moderate and moderately-severe levels of upper-limb impairment following stroke are able to use gaming technologies as a means of delivering upper-limb rehabilitation. Future studies should address issues of acceptability, feasibility, and efficacy of personalised gaming technologies for delivery of upper-limb stroke rehabilitation in the home environment. Findings from this study can be used to develop future games and activities suitable for use in stroke rehabilitation.